2009
DOI: 10.1002/ajmg.a.32707
|View full text |Cite
|
Sign up to set email alerts
|

A patient with early onset Huntington disease and severe cerebellar atrophy

Abstract: We report on a girl with early onset Huntington disease (HD). Her initial symptoms at 2 years of age included oral motor dysfunction and gait disturbance. Magnetic resonance imaging of the head revealed severe atrophy of both the vermis and the cerebellar cortex in addition to the common findings of basal ganglia including the caudate nuclei, putamen, and globus pallidus. Molecular analysis showed 160 CAG repeats in the HD gene. This mutation was inherited from her mother who was also affected, with a HD CAG e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 14 publications
0
26
0
Order By: Relevance
“…Within the field, early studies suggested a role for the cerebellum in HD as shown by cerebellar atrophy in both patients and mouse models (Kageyama, Yamamoto et al 2003; Fennema-Notestine, Archibald et al 2004; Ruocco, Lopes-Cendes et al 2006; Sakazume, Yoshinari et al 2009; Nicolas, Devys et al 2011). However, due to striatal atrophy and the marked loss of medium spiny neurons observed in HD patients and animal models, there has been a focus on the striatum in many studies of HD etiology.…”
Section: Discussionmentioning
confidence: 99%
“…Within the field, early studies suggested a role for the cerebellum in HD as shown by cerebellar atrophy in both patients and mouse models (Kageyama, Yamamoto et al 2003; Fennema-Notestine, Archibald et al 2004; Ruocco, Lopes-Cendes et al 2006; Sakazume, Yoshinari et al 2009; Nicolas, Devys et al 2011). However, due to striatal atrophy and the marked loss of medium spiny neurons observed in HD patients and animal models, there has been a focus on the striatum in many studies of HD etiology.…”
Section: Discussionmentioning
confidence: 99%
“…Second, their manifestations were atypical, in which rigidity, bradykinesia, intellectual decline, behavior change, frequent falls, speech impairment, seizures, and ataxia were the initial or predominant (7,14,(19)(20)(21)(22)(23)(24). Fourth, the atrophies in cerebral cortex, striatum or cerebellum and increased density in T 2 -weighted signal in caudate and putamen nuclei in MRI were characteristic imaging features (12,23,28). Third, paternal transmission was predominant pattern of inheritance (19).…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, case studies have shown that JOHD presents not only with the cardinal features of adult onset HD (rigidity, chorea, dementia) but also additional symptoms including a higher occurrence of seizure activity (Hattori, Takao et al 1984; Ruocco, Lopes-Cendes et al 2006). In JOHD, there are multiple reports of cerebellar involvement, atrophy and dysfunction, including fMRI studies showing an incidence of cerebellar atrophy in these most severe patients (Ruocco, Lopes-Cendes et al 2006; Sakazume, Yoshinari et al 2009; Nicolas, Devys et al 2011). Therefore, it is possible that these results may not extend to adult-onset HD mouse models; experiments with HD adult-onset mouse models are required to address this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Conflicting reports have been made on the pathology of the cerebellum in HD which range from the region being considered unaffected (Van Raamsdonk, Warby et al 2007; Carroll, Lerch et al 2011) to the cerebellum being an important part of the disease progression (Rodda 1981; Rosas, Koroshetz et al 2003; Fennema-Notestine, Archibald et al 2004; Ruocco, Lopes-Cendes et al 2006). The cerebellum appears to be more commonly affected in juvenile HD as exhibited by a loss in overall cerebellar volume (Kageyama, Yamamoto et al 2003; Fennema-Notestine, Archibald et al 2004; Ruocco, Lopes-Cendes et al 2006; Sakazume, Yoshinari et al 2009; Nicolas, Devys et al 2011). It is imperative to explore cerebellar pathology in animal models of HD to determine the involvement of this brain region in the pathogenesis of HD.…”
Section: Introductionmentioning
confidence: 99%